Shear behavior of concrete beams reinforced with steel or GFRP reinforcement without stirrups - Kotynia, R. (2017)
The paper presents results of experimental test carried out on 12 T-shape concrete beams reinforced with FRP or steel bars without stirrups. The beams were differed in a type of longitudinal reinforcement made of glass fibers reinforced polymer (GFRP - 7 beams) and steel (5 beams), the longitudinal reinforcement ratio, a diameter of bars and a number of reinforcement layers (one or two). All beams failed in shear. GFRP reinforced beams failed due to gradual development of diagonal cracks, while in the beams with steel reinforcement diagonal crack developed rapidly leading an abrupt failure. Steel reinforced beams had a higher load capacity than the beams with GFRP bars. Beneficial influence a number of reinforcement layers was confirmed especially for longitudinal reinforcement ratio of 1.80%. While for reinforcement ratio about 1.0%, there was no difference of the shear capacity.